Applying the Happenstance Learning Theory to Involuntary Career Transitions. Issue 1 (28th February 2013) - Krumboltz, John D.; Foley, Pamela F.; Cotter, Elizabeth W.
<x xml:space="preserve">Abstract</x> The happenstance learning theory (HLT) proposes a model of career counseling that helps clients to build more satisfying personal and work lives. Although reflective listening remains an essential part of the process, HLT is an action‐oriented approach to helping clients to both create and benefit from unplanned events. Success is measured not by what happens during the counseling interview but by what the client experiences in the real world during and after counseling. A case study illustrates how HLT might be applied with a client who has been laid off after 20 years on the job.